Music and Sufisme (Sufism Values in Ebiet G. Ade’s Selected Songs ) - Tahir, Gustia (Al-Hikmah, 2022)
There are many ways for humans to approach God. Religion is one of them. In religion, there is a teaching called Sufism. Sufism is a legacy of classical Islamic treasures that still exist today. This is because Sufism can provide a way for humans to know God better and be closer to Him. In the Sufi tradition, music is one of the media to feel closer to God, because music can carry the human soul into the recesses of the heart. This paper aims to reveal the content of Sufism values ​​in Ebiet G. Ade’s songs. This research is a qualitative research with a hermeneutic interpretation approach. This research found that in Ebiet G. Ada’s song, there are a number of lyrics that can bring listeners closer to their God.